Fisiografia e uso da terra de uma bacia hidrográfica em área de afloramento do sistema aquífero Guarani (SAG): o caso do Ribeirão do Jacú, Tejupá/SP (UGRHI-14)SP - Reissler, Joyce [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
With the increasing demand for fuel, food and fiber that follows population growth, the effort to provide sufficient water for agriculture causes additional pressure on the environment. In this scenario, a groundwater resources has been highlighted as a good choice of water quality, due to the possibility of exploration in places near the production areas. The conflicting interests between the use of the water and the protection of strategic sources reinforce the needs for a legislation adaptation looking for a better territorial organization and a sustainable water resources management. This study aimed to map land use in an outcrop area of the Guarani Aquifer System (SAG) and generate information for a better planning and discussion of public policies for groundwater resources conservation in areas with irrigated agricultural production. The study area was the Ribeirão do Jacú watershed, in the municipality of Tejupá - SP, Brazil, located entirely in the outcrop area of SAG, therefore, a high vulnerability region. From supervised satellite image classification of land use and occupation using Geographic Information System (GIS), it was possible to identify and to quantify the major activities developed and the conflicts of the actual land use in the watershed in the period between 2002 and 2011. The results showed the presence of agricultural and livestock systems in Permanent Preservation Areas (PPA) and an improvement of irrigated agriculture in areas closed to the outflow of the basin, indicating a trend of local production intensification. With this information, it was...

Com a crescente demanda por combustíveis, alimentos e fibras que acompanha o crescimento populacional, o esforço para oferecer água suficiente para a agricultura e prover insumos provoca pressão adicional sobre o meio ambiente. Neste cenário, recursos hídricos subterrâneos têm ganho destaque, sendo uma opção de qualidade de água e pela facilidade de captação próxima às áreas de produção. Interesses conflitantes entre o uso da água e a proteção de mananciais estratégicos reforçam a necessidade de adequação da legislação para que se busque um melhor ordenamento do território e um manejo sustentável dos recursos hídricos. O objetivo deste trabalho foi mapear o uso da terra em área de afloramento do Sistema Aquífero Guarani (SAG) e gerar informações para o melhor planejamento e discussão de políticas públicas de conservação dos recursos hídricos subterrâneos em áreas de alta produção agrícola irrigada. A área de estudo foi a Bacia do Ribeirão do Jacú, no município de Tejupá - SP, localizada integralmente em área de afloramento do SAG, portanto, região considerada vulnerável. Com a classificação supervisionada do uso da terra, através de um Sistema de Informações Geográficas (SIG), pode-se identificar e quantificar as principais atividades desenvolvidas e os conflitos de uso da terra na bacia entre os períodos de 2002 e 2011. Os resultados demonstram a apropriação de sistemas agrícolas e pecuária em Área de Preservação Permanente (APP) e um avanço da agricultura irrigada nas áreas próximas ao exutório da bacia, apontando uma tendência de ...
Physiography and Land Use of a watershed in a Guarani Aquifer System outcrop area: The Ribeirão do Jacú wathershed case study, Tejupá / Sp (Ugrhi-14)
Keywords: Sistemas de informação geografica; Abastecimento de água; Recursos naturais - Conservação; Proteção ambiental; Agriculture Environmental aspects; São Paulo (Estado)